Muhasabah as a Regulative Effort for Digital Natives who Identified Fear of Missing out (FoMO) - Uasni, Zunea Farizka Azyza Harro; Uyun, Qurotul; Annatagia, Libbie (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Digital native is known as the generation that is literate about digital technology and makes the internet a part of their life. Social media as a tool of connectedness on the internet for digital native can always be connected to each other. The high-level increase of social media usage causes digital native always wanting to know the circumstances and experiences accomplished by others through accessing social media. This desire has the possibility to become a fear when anxiety and worries intensively arise due to loss of news or events experienced by others. This fear is referred to as fear of missing out (FoMO). The method in this study is the study of literature (literature review). The data obtained are compiled, analyzed, and concluded so as to obtain conclusions regarding the study of literature. This study tries to illustrate that muhasabah as a regulative effort can help the digital native identified by FoMO in order to contemplate, introspect and understand the state of the self as a form of worship towards God and is determined to change the state of the self to be better than before with Islam way.